Alzheimer Lesions in the Autopsied Brains of People 30 to 50 Years of Age. Issue 3 (September 2015) - Pletnikova, Olga; Rudow, Gay L.; Hyde, Thomas M.; Kleinman, Joel E.; Ali, Sabeen Z.; Bharadwaj, Rahul; Gangadeen, Salina; Crain, Barbara J.; Fowler, David R.; Rubio, Ana I.; Troncoso, Juan C.
<x xml:space="preserve">Abstract</x> Objective: To test the hypothesis that asymptomatic Alzheimer disease lesions may appear before 50 years of age. Background: Alzheimer disease has an asymptomatic stage during which people are cognitively intact despite having substantial pathologic changes in the brain. While this asymptomatic stage is common in older people, how early in life it may develop has been unknown. Methods: We microscopically examined the postmortem brains of 154 people aged 30 to 39 years (n=59) and 40 to 50 years (n=95) for specific Alzheimer lesions: beta-amyloid plaques, neurofibrillary tangles, and tau-positive neurites. We genotyped DNA samples for the apolipoprotein E gene (APOE). Results: We found beta-amyloid lesions in 13 brains, all of them from people aged 40 to 49 with no history of dementia. These plaques were of the diffuse type only and appeared throughout the neocortex. Among these 13 brains, five had very subtle tau lesions in the entorhinal cortex and/or hippocampus. All individuals with beta-amyloid deposits carried one or two APOE4 alleles. Among the individuals aged 40 to 50 with genotype APOE3/4, 10 (36%) had beta-amyloid deposits but 18 (64%) had none. Conclusions: Our study demonstrates that beta-amyloid deposits in the cerebral cortex appear as early as 40 years of age in APOE4 carriers, suggesting that these lesions may constitute a very early stage of Alzheimer disease. Future preventive and therapeutic measures for this disease may have to be stratified by risk factors like APOE genotype and may need to target people in their 40s or even earlier.